2019
DOI: 10.1149/09208.0361ecst
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Investigation of Polyphenylene Sulfide Polymer-Graphite Bipolar Plates for Fuel Cell Application

Abstract: In this work two compression molded commercial polyphenylene sulfide (PPS) polymer-graphite composite bipolar plates (BPPs) with 15 and 20 % of polymer binder material from two different manufacturers were employed for an analytical comparative investigation using physical and electrochemical analysis. Chemical stability of BPPs was investigated after storage in phosphoric acid. Corrosion resistance and electrochemical aging of the BPPs were studied by using linear sweep voltammetry, cyclic voltammetry and ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
2
1
0
Order By: Relevance
“…For set-up A, it can be observed that the pristine sample has a rather smooth surface with rms of 824 nm in comparison with the aged with rms of 1114 nm, which shows randomly distributed dents within the composite structure ( Figure 4). Comparable roughness values with graphite composite-based bipolar plates were reported in the literature [31,32]. Analogously, detectable differences can be determined for set-up B, while the pristine samples also show a more homogeneous surface with rms of 897 nm before aging and 1628 nm after the procedure.…”
Section: Methods Isupporting
confidence: 78%
See 1 more Smart Citation
“…For set-up A, it can be observed that the pristine sample has a rather smooth surface with rms of 824 nm in comparison with the aged with rms of 1114 nm, which shows randomly distributed dents within the composite structure ( Figure 4). Comparable roughness values with graphite composite-based bipolar plates were reported in the literature [31,32]. Analogously, detectable differences can be determined for set-up B, while the pristine samples also show a more homogeneous surface with rms of 897 nm before aging and 1628 nm after the procedure.…”
Section: Methods Isupporting
confidence: 78%
“…It can be concluded that the surface morphology and structure of BPP are closely related to the corrosion behaviour in both set-ups and can be distinguished using SEM and confocal microscopy. The dependency of roughness values and the corrosion current is also shown by Dushina et al, where similar polymer graphite BPPs were investigated in terms of electrochemical aging, and surface roughness equal to 967 nm was reported [31]. The results generated by two different corrosion cells demonstrated the importance of the set-up and the arrangement of electrodes for research on corrosion behaviour.…”
Section: Methods Isupporting
confidence: 55%
“…Polyphenylene sulfide (PPS) has excellent chemical resistance, low degradation at high temperatures, and high rigidity. It also shows remarkable fatigue endurance and creep resistance, which have attracted extensive attention to it regarding its use for BPs [ 72 , 73 , 74 ]. However, PPS has a low elongation to break and low conductivity [ 75 , 76 ].…”
Section: Carbon-reinforced Polymer Compositesmentioning
confidence: 99%